Induksi Persalinan Dengan Kejadian Asfiksia Pada Bayi Baru Lahir - Reni Tri Lestari; Yuniar Wardani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: The infant mortality rate in developing countries an estimated 4-9 million, the cause was asphyxia newborns with the number of events 20% of all infant deaths. Infant Mortality Rate in Yogyakarta was 19/1000 life births in 2007. Asphyxia is a first of cases infant who were treated in Panembahan Senopati Bantul Hospital in 2010 and there were 272 labor induction with 225 incedent cases of asphyxia.Objective: The aim of this study to know the relationship between the incidence of induction of labor with asphyxia in newborns in Panembahan Senopati Bantul hospital in 2012.Method:This type of research is a case control design, with a 2:2 ratio of cases and controls is 160: 160. The sample is all women who gave birth vaginally. The study uses secondary data, analysis of data using univariate and bivariate analysis.Result: The result X2= 8,76, the price of db table X2=1 and α=0,05 is 3,84. It means X2 calculated value >X2 table, it can be concluded that there was a significant correlation labor induction with incident of asphyxia newborns. Odds ratio value 2,36 can be concluded that the asphyxia was a risk factor.Conclusion: Patient who labor induction was estimed to 2,36 times the baby suffered asphyxia than in patients who do not induce labor.Key words: labor induction, asphyxia newborn